A survey of midlands state university students’ portrait of an ideal marriage partner - Machingura, Moffat (Midlands State University, 2017)
The study runs along the topic “A survey of Midlands State University students’ portrait of an ideal marriage partner” based upon the problem statement that ignorance of characteristics one expects and is expected of in a marriage partner can result in miscalculated social commitments and non-satisfying relationships. The ultimate purpose of findings being to chart a course to happier and longer lasting relationships, a matter critically crucial upon the current background of increasing levels of national, continental and global break-ups and divorce rates. This study defines attractiveness, and introduces factors that lead to attractiveness. It further introduces the Stimulus Value Role theory with attempt to show how life partner selection lies beyond interpersonal attraction alone. This is a study of 340 Midlands State University students across ages 19 to 26 and across 11 degrees. The study finds preferences for Physical Attractiveness, Social Roles, Geographical Area, Academic Qualifications, Levels of Affluence and Sexual Lifestyle to be generally similar variables in the selection of life partners across the given ages and sexes. The study also finds a shift of expected social roles from the traditionalperspective.